1969
DOI: 10.4039/ent101561-6
|View full text |Cite
|
Sign up to set email alerts
|

ON THE BEHAVIOR AND ECOLOGY OF THE FACE FLY, MUSCA AUTUMNALIS (DIPTERA: MUSCIDAE)

Abstract: The face fly, Musca autumnalis De Geer, is continuously present in the field at Guelph, Ont., from April to late October, with peak populations occurring near 1 August. The flies enter buildings only to hibernate, the females doing so in an unfertilized, nulliparous condition. The flies feed only during the daylight hours and primarily on cattle and horses. Infestations on these hosts arc subject to wide daily and hourly variation dependent on temperature, light, precipitation, wind, and behavior of the host.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 16 publications
(14 reference statements)
1
30
0
Order By: Relevance
“…Teskey (1969) reported that animals in the beef herd he studied in Ontario were normally more heavily infested with face flies than the dairy cows. This difference is likely due to differences in management between beef and dairy cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Teskey (1969) reported that animals in the beef herd he studied in Ontario were normally more heavily infested with face flies than the dairy cows. This difference is likely due to differences in management between beef and dairy cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In the housefly, this was paralleled by seasonal shifts in size within a population, with larger flies occurring during the winter, such that geographic and seasonal adaptation coincided in pattern and nearly in magnitude. We have no similar estimates for seasonal variation in the face fly, but we conjecture that it may not be as important since its activity pattern is limited from about May through October when it seeks refuge in buildings (Hammer, 1942;Teskey, 1969), and would thus not be exposed to recurring selection as the housefly in southern localities.…”
Section: Discussionmentioning
confidence: 99%
“…In any event, the coincidence of these two patterns suggests that climate could play a major role in limiting the face fly to northern latitudes rather than parasites or predators as studied by Valiela (1969) and Burton and Turner (1970). Indeed, the local densities of adult face flies are affected by humidity and wind, restricting them to areas of lower humidy and wind in the field (Hammer, 1942;Depner, 1969;Teskey, 1969), a reaction also evident in choice tests in the laboratory (Roberts and Pitts, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…However, the face fly puparia were in a porous layer of vermiculite; and as the parasites did not burrow into sand or fine soil experimentally, parasites of pupae probably attack M. autumnalis much less frequently under natural conditions, where many of the fly pupae are in the soil (Teskey 1969). However, the parasite complex of face fly in eastern Ontario differs qualitatively in several respects from that recorded in south-western Ontario, New Hampshire, Virginia, and Missouri.…”
Section: Discussionmentioning
confidence: 83%
“…Attempts by the United States Department of Agriculture to establish insect and mermithid parasites from Europe were unsuccessful (Hayes and Turner 1971), and have now been discontinued. To date, the only report of face fly parasitism in Canada is Teskey's (1969) record of Aphaereta pallipes (Say) (Hymenoptera: Braconidae) and Xyalophora sp. Prerequisites to this procedure are, of course, determination of the identity and distribution of the native parasite species and evaluation of their feasibility for and potential control value in inundation programmes.…”
Section: Introductionmentioning
confidence: 99%